Altimetria com topografia convencional e sensoriamento remoto - Pinto, Leandro de Mello (2012)
The altimetry of the surface terrain for many decades has been achieved almost exclusively by conventional surveying. The advancement of technology allowed the development of space missions and the creation of artificial satellites, making the science of remote sensing to expand exponentially. The SRTM (Shuttle Radar Topographic Mission) and ASTER GDEM (Advanced Spaceborne Thermal Emission and Reflection Radiometer) are spatial programs that provide altitude information of almost the entire globe. The program Google Earth uses that information, and provides for its users in a practical and rapid way. For ease of access to data from these techniques, many users use them without knowing the geometric problems existing in these products, which can compromise the quality of results obtained through these techniques. Therefore, there is a need for a prior evaluation to assess the quality and workability for each method. In this context, the objective was to analyze the accuracy of three ways of obtaining altitude: by SRTM, ASTER and Google Earth, comparing them with conventional surveying and with GPS, because they are more established techniques. To this end, two surveys were performed in situ, one using a GPS receiver and the other by conventional topography, where the heights of the points were compared with the heights obtained by the three methods analyzed, resulting in discrepancies. The results show that the data from the SRTM provided by Embrapa Monitoring by Satellites through the Project Brasil em Relevo are more accurate than ASTER data and Google Earth, moreover, was also found that the Kriging interpolation technique has best results for altimetric spatial data.